2016
DOI: 10.1101/045047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic and Genomic Characterization of a Yeast Model for Ogden Syndrome

Abstract: Naa10 is a N α -terminal acetyltransferase that, in a complex with its auxiliary subunit Naa15, co-translationally acetylates the α-amino group of newly synthetized proteins as they emerge from the ribosome. Roughly 40-50% of the human proteome is acetylated by Naa10, rendering this an enzyme with one of the most broad substrate ranges known. Recently, we reported an X-linked disorder of infancy, Ogden syndrome, in two families harboring a c.109T>C (p.Ser37Pro) variant in NAA10. In the present study we perform… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…Conversely, the turnover rates of mitochondrial ribosomal proteins showed a mixed behavior suggesting that an enhanced synthesis of mitochondrial ribosomal proteins is induced as a response of impaired mitochondrial function. This phenomenon has also been described in previous ribosome profiling and RNA-seq studies, which showed elevated translation of nuclear-encoded genes of mitochondrial ribosomal proteins in NatA-lacking strains ( 8, 54, 57 ).…”
Section: Resultssupporting
confidence: 82%
“…Conversely, the turnover rates of mitochondrial ribosomal proteins showed a mixed behavior suggesting that an enhanced synthesis of mitochondrial ribosomal proteins is induced as a response of impaired mitochondrial function. This phenomenon has also been described in previous ribosome profiling and RNA-seq studies, which showed elevated translation of nuclear-encoded genes of mitochondrial ribosomal proteins in NatA-lacking strains ( 8, 54, 57 ).…”
Section: Resultssupporting
confidence: 82%
“…This discrepancy between the biochemical results for p.Arg83Cys missense in NAA10 from the reductionistic approach focusing on NatA enzymatic acetylation of a substrate peptide in a test tube compared to the phenotypic presentation in the humans with this same change can best be addressed in the future with patient-derived cell lines and/or animal models. An alternative has been to study the human mutations in the human genes expressed in a S. cerevisiae model knocked out for endogenous yeast Naa10 and/or Naa15 (Van Damme et al 2014; Max J. Dörfel et al 2017; H. Cheng et al 2018), although S. cerevisiae is a much simpler unicellular organism that does not represent the complexity of a human cell or a human being.…”
Section: Discussionmentioning
confidence: 99%
“…The identical variant was recently reported in a third family (Gogoll et al 2021). There is a S. cerevisiae model for the Naa10 Ser37Pro mutant, in which that variant impairs NatA complex formation and leads to a reduction in both NatA catalytic activity and functionality (Van Damme et al 2014; Max J. Dörfel et al 2017). Furthermore, OS patient-derived cells have impaired in vivo NTA of a few NatA substrates (Myklebust et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the X-linked Ogden syndrome (OS) (25,26) shows the most severe pathological features such as infant lethality and has reduced NatA catalytic activity. In a Saccharomyces cerevisiae model for the Naa10 Ser37Pro mutant, the mutation impairs NatA complex formation and leads to a reduction in NatA catalytic activity and functionality (27,28). Further, OS patient-derived cells have impaired NTA in vivo of some NatA substrates (25).…”
Section: Introductionmentioning
confidence: 99%